Protonska uganka - Umek, Luka (Matrika, 2021)
The proton is the basic building block of matter. It is essential to understand its properties well in order to study complex systems of particles, nuclei and matter in general. Despite it being a subject of intense research over the last 60 years, there are still many questions left unanswered. One of the more prominent is the question of the proton charge radius - results of different measurements provide values that differ significantly. Today this discrepancy is known as the proton radius puzzle. In this article the main methods of determining the proton charge radius, the motivation for such research, and findings of some latest studies are presented and discussed.
Keywords: jedrska fizika; nabojni polmer protona; nuclear physics; proton charge radius; proton radius puzzle; protonska uganka